Coming to life - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Coming to life: biotechnology in African economic recovery edited by C Juma, J Mugabe and P Kameri-Mbote 1995 192pp ISBN 9966 41 087 2 price Ksks350, UKL 13.95